Parametric study on efficient formation flying for a blended-wing UAV - Shin, Hyo-Sang; Antoniadis, Antonis F.; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper investigates aerodynamic performance improvements of formation flight at transonic speeds for a medium size Unmanned Aerial Vehicle (UAV). The metric for assessing the aerodynamic improvement of formation flight is the computed drag. The total drag for each formation configuration is compared with a single UAV, where a final drag reduction percentage is estimated. The evaluation of the aerodynamic performance is conducted by employing an in-house Computational Fluid Dynamics (CFD) solver, grid generation and post processing tools. For critical understanding of the tendency of the formation efficiency depending on main parameters, broad formation configurations are analysed. The parameterisation includes number of aircraft, proximity and formation shape. Full realisation of the benefit predicted would need to be proven in the real world, but there is sufficient confidence to suggest that it exists: the empirical parametric analysis suggests that formation flight can improves aerodynamic performance and formation configuration greatly influence the degree of improvement.